Serial Case of CT Scan Imaging in Fracture of Midface Region - Martono, Budi; Asih, Made Widhi; Sudiatmika, Dewa Gde Mahiswara (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): JBN (Jurnal Bedah Nasional)DO - 10.24843/JBN.2024.v08.i02.p06, 2024)
Background: Fractures in the face region are frequently seen in motor vehicle accidents, as the face is highly exposed during such incidents. Motor vehicle accidents are common in Bali, with fracture of the face region is the 2nd most common injury found in radiologic examination. Computed tomography (CT) scans are crucial for assessing these fractures, allowing for an accurate evaluation of severity to plan the patient treatment. Case: We present serial cases CT scan images of complex midface fractures such as Le Fort, tripod, NOE and orbital wall fracture and its characteristic imaging on CT-imaging. Conclusions: CT scan may guide treatment plans aimed at minimizing disability and enhancing the patient's quality of life. Understanding the imaging characteristics of midface fractures is thus essential for effective diagnosis and management.